DIGITAL ETHICS IN SOCIAL MEDIA TO MAINTAIN AND STRENGTHEN THE NATION'S SOCIO-CULTURAL VALUES - Tantri Relatami; Dela Anjelawati; Kartikawati, Dwi (PT. Jurnal Center Indonesia Publisher, 2026)
Social interaction that occurs on social media serves not only as a means of social interaction but also as a primary platform for information dissemination and public opinion formation. However, the ease of access and interactivity of social media also pose serious challenges regarding the application of digital ethics. Freedom in social media is not limitless freedom. Digital ethics involves principles and norms that govern user behavior in creating, producing, and distributing content with full responsibility. The 2020 Digital Civility Index (DCI) report regarding changes in community behavior in social media usage and forms of communication interaction places Indonesia at the lowest rank in the civility index. Incivility in social media conduct by the community results in significant vulnerability and threats of division, unrest, and conflict within society. Digital ethics involves principles and norms that govern user behavior in creating, producing, and distributing content with full responsibility. Ethics and morals have an attachment to one another. Keywords: Digital Ethics, social media, values, socio-cultural